Deals, Datus and Dayaks Sarawak and Brunei in the making of Malaysia - Leigh, Michael (Strategic Information and Research Development Centre, 2018)
This book tells the story of Malaysia's formation and its early struggle for survival. A treasure trove of recently de-classified records from the UK National Archives and the US Consulate in Kuching, demonstrate how the British, Singapore and Malayan governments seized upon the Brunei revolt, and Indonesian attacks across the Sarawak border, to justify their extensive use of coercive measures against the strongest opponents of the federation proposal, and to reinforce strong messaging that forming Malaysia was the best available future for Sarawak, Sabah and Singapore too. Despite all of those efforts, new archival evidence shows how the political situation in Sarawak almost caused Malaysia to be aborted at the last minute. The book then goes on to document how strong international and internal pressures throughout 1964 and 1965 meant that the very survival of Malaysia was in doubt.